PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, KEMAMPUAN KERJA, DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN LUWU TIMUR - Santi Sappaile (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to: (1) test and analyze the influence of work discipline, work motivation, work ability, and work experience on employee performance at the East Luwu Regency Health Office; (2) test and analyze the simultaneous (joint) influence of work discipline, work motivation, work ability, and work experience on employee performance at the East Luwu Regency Health Office. The research was conducted at the East Luwu Regency Health Office. The population consisted of 126 individuals. The research method employed was observation. The data types used were both qualitative and quantitative. Data sources included primary and secondary data. The analysis methods comprised descriptive analysis, correlation coefficient, and validation testing using simple correlation, processed with IBM SPSS software. The hypothesis testing results indicate that: (1) work discipline has a positive influence on employee performance; (2) work motivation has a positive influence on employee performance; (3) work ability has a positive influence on employee performance; (4) work experience has a positive influence on employee performance; (5) the four variables simultaneously have a positive influence on employee performance at the East Luwu Regency Health Office. Keywords : Discipline, Motivation, Ability, Experience, Performance, Health Office